Patient localisation with smart phones using public cloud. (2016) - Geetha, V.
Today's world scenario has made evolution in healthcare domain as inevitable. Large number of people expires due to sudden medical emergencies such as heart attacks and accidents. However, it is very difficult to extend immediate medical care at all places and at all times. Research is going on to improve the delivery time of medical care. However, patient localisation poses a major problem. In this paper, a solution is proposed for ubiquitous patient localisation with smart phones using public clouds based on GPS tracking. As the current cloud infrastructure does not support sensing requests, a smart sensing as a service (S 2 aaS) framework is proposed to be added to the cloud infrastructure. The proposed system has the advantages of minimal interaction and high reliability. Also, the patients need not remember their medical history or contact details of nearby hospitals. The performance results of the proposed system are also evaluated.